Diagnostic evaluation for interventional bronchoscopists and radiologists in lung cancer practice - Lau, Eddie; Ware, Rob; Herth, Felix (Respirology, 2015)
The global epidemic of lung cancer shows no signs of abating. It is generally accepted that accurate and cost-efficient diagnostic evaluation is the first important step to achieve the best outcomes of treatment. This is true in the context of disease confirmation, treatment planning, treatment monitoring, detection of and management of treatment failure or prognostication. Fortunately, major advances in the diagnostic evaluation of lung cancer have been made in the past three decades allowing more patients to get the appropriate treatment at the right time. This paper outlines how computed tomography, positron emission tomography/computed tomography and endobronchial ultrasound contribute to lung cancer management and discuss their strengths and weaknesses and their complimentary roles at different stages of lung cancer management.
Gesehen am 09.06.2020